Supply of neuraminidase inhibitors related to reduced influenza A (H1N1) mortality during the 2009–2010 H1N1 pandemic: summary of an ecological study. (27th August 2013) - Miller, Paula E.; Rambachan, Aksharananda; Hubbard, Roderick J.; Li, Jiabai; Meyer, Alison E.; Stephens, Peter; Mounts, Anthony W.; Rolfes, Melissa A.; Penn, Charles R.
Abstract : When the influenza A (H1N1) pandemic spread across the globe from April 2009 to August 2010, many WHO Member States used antiviral drugs, specifically neuraminidase inhibitors (NAIs) oseltamivir and zanamivir, to treat influenza patients in critical condition. Antivirals have been found to be effective in reducing severity and duration of influenza illness, and likely reduce morbidity; however, it is unclear whether NAIs used during the pandemic reduced H1N1 mortality. To assess the association between antivirals and influenza mortality, at an ecologic level, country‐level data on supply of oseltamivir and zanamivir were compared to laboratory‐confirmed H1N1 deaths (per 100 000 people) from July 2009 to August 2010 in 42 WHO Member States. From this analysis, it was found that each 10% increase in kilograms of oseltamivir, per 100 000 people, was associated with a 1·6% reduction in H1N1 mortality over the pandemic period [relative rate (RR) = 0·84 per log increase in oseltamivir supply]. Each 10% increase in kilogram of active zanamivir, per 100 000, was associated with a 0·3% reduction in H1N1 mortality (RR = 0·97 per log increase). While limitations exist in the inference that can be drawn from an ecologic evaluation, this analysis offers evidence of a protective relationship between antiviral drug supply and influenza mortality and supports a role for influenza antiviral use in future pandemics. This article summarises the original study described previously, which can be accessed through the following citation: Miller PE, Rambachan A, Hubbard RJ, Li J, Meyer AE, et al . (2012) Supply of Neuraminidase Inhibitors Related to Reduced Influenza A (H1N1) Mortality during the 2009–2010 H1N1 Pandemic: An Ecological Study. PLoS ONE 7(9): e43491.